The connected classroom. - Garcia, Angelo G.
All these new developments prove that the world is practically at the doorstep of the fully-digital classroom...
Keywords: Dell Computer Corp; Digital classroom; Ergotron TeachWell Mobile Digital Platform; Connected Classroom